the solution is
![(x^{}-2)^2+(y+4)^2=16](https://img.qammunity.org/2023/formulas/mathematics/college/o0mg482lcts3v01y81h9e7c1uxwijgziv2.png)
the center is in (x,y)=(2,4)
the radius is 4
to solve this, first we agroup the x's and y's,
![(x^2-4x)+(y^2+8y)=-4](https://img.qammunity.org/2023/formulas/mathematics/college/1zwgj7dg9p4xhcjiw8fdhrw4k9su0ijh09.png)
normaly, we would need to divide the whole equation by the coeficient of the squares
in this case the coeficient is 1 so we don't need to do that
now, we need to look at the coeficient of the x and y (not squared)
for x is -4 and for y is +8
we divide them bi two, and square them
-4/2=-2 => -2^2=4
8/2=4 => 4^2=16
and now we add this terms in the parentheses and add the to the right side of the equation
![(x^2-4x+4)+(y^2+8y+16)=-4+4+16](https://img.qammunity.org/2023/formulas/mathematics/college/38gxvob7n48ike696hi7uktq1lh77gf2ml.png)
now, we need to simplify the parentheses and let them expresed as binomial squares
![(x-2)^2+(y+4)^2=16](https://img.qammunity.org/2023/formulas/mathematics/high-school/m4g4bsfzsk8q2yatcbalbynrsvaz7noddf.png)
and thats the equation. now the term inside the parentheses that aren't x or y, tell us the center.
center (x,y)=(2,-4)
and the radius is the square root of the term in the right side
![\text{radius: }\sqrt[]{16}=4](https://img.qammunity.org/2023/formulas/mathematics/college/9re5wm7nml8lv6ruyjhlnmmhzgxnvv8i5g.png)